2017
DOI: 10.1021/acs.nanolett.7b00768
|View full text |Cite
|
Sign up to set email alerts
|

Giant Gating Tunability of Optical Refractive Index in Transition Metal Dichalcogenide Monolayers

Abstract: We report that the refractive index of transition metal dichacolgenide (TMDC) monolayers, such as MoS2, WS2, and WSe2, can be substantially tuned by > 60% in the imaginary part and > 20% in the real part around exciton resonances using CMOS-compatible electrical gating. This giant tunablility is rooted in the dominance of excitonic effects in the refractive index of the monolayers and the strong susceptibility of the excitons to the influence of injected charge carriers. The tunability mainly results from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 47 publications
2
92
2
Order By: Relevance
“…This modulation depth observed in our device is among the best for TMDs based modulators. [4][5][6]37 The changes observed in Fig. 4c, d are attributed to the V g induced refractive index changes (Fig.…”
Section: Ellipsometry Measurementsmentioning
confidence: 81%
See 2 more Smart Citations
“…This modulation depth observed in our device is among the best for TMDs based modulators. [4][5][6]37 The changes observed in Fig. 4c, d are attributed to the V g induced refractive index changes (Fig.…”
Section: Ellipsometry Measurementsmentioning
confidence: 81%
“…We found that the peak positions of E 1 2g and A 1g modes were largely unaffected by the V g within the experimental error of ±0.2 cm −1 while Raman intensities of both E 1 2g and A 1g modes for Au/Si 3 N 4 / MoS 2 hybrid nanostructure changed significantly with the applied gate voltage. According to previous studies, 5 the intensity ratio of the Raman peaks could be used to explore exciton properties (bandgap renormalisation, damping factors, oscillator strengths associated with the excitons) of a MoS 2 monolayer. For example, the ratio of intensities of the E 1 2g and A 1g peaks (I E2g /I A1g ) of MoS 2 could be used to identify the number of layers in MoS 2 ( Fig.…”
Section: Sample Preparation and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we note that electrostatic gate tunable electro-absorption has recently been observed in silicon backgated TMDC planar (normal incidence, non-waveguide) device geometries. Evidence of such are reported by Yu et al [5], or ITO backgated Hafnia/MoS2 structures fabricated by Vella et al [6]. In this Letter, we offer an alternative method of electro-optic modulation through the use of a functionalized hollow core fiber waveguide.…”
mentioning
confidence: 57%
“…This was confirmed by replacing the film with WS2. The refractive index was changed to 4.80, as discussed 11 Figure 2b when the fiber has no deposition inside. As can be seen, a single resonance occurs at around the 600nm mark.…”
Section: Simulations Resultsmentioning
confidence: 99%